Breast implant associated anaplastic large cell lymphoma: The UK experience. Recommendations on its management and implications for informed consent. Issue 8 (August 2017) - Johnson, L.; O'Donoghue, J.M.; McLean, N.; Turton, P.; Khan, A.A.; Turner, S.D.; Lennard, A.; Collis, N.; Butterworth, M.; Gui, G.; Bristol, J.; Hurren, J.; et al.
Abstract: Background: Breast implant-associated anaplastic large-cell lymphoma (BIA-ALCL) is a rare, Non-Hodgkin lymphoma arising in the capsule of breast implants. BIA-ALCL presents as a recurrent effusion and/or mass. Tumours exhibit CD30 expression and are negative for Anaplastic Lymphoma Kinase (ALK). We report the multi-disciplinary management of the UK series and how the stage of disease may be used to stratify treatment. Methods: Between 2012 and 2016, 23 cases of BIA-ALCL were diagnosed in 15 regional centres throughout the UK. Data on breast implant surgeries, clinical features, treatment and follow-up were available for 18 patients. Results: The mean lead-time from initial implant insertion to diagnosis was 10 years (range: 3–16). All cases were observed in patients with textured breast implants or expanders. Fifteen patients with breast implants presented with stage I disease (capsule confined), and were treated with implant removal and capsulectomy. One patient received adjuvant chest-wall radiotherapy. Three patients presented with extra-capsular masses (stage IIA). In addition to explantation, capsulectomy and excision of the mass, all patients received neo-/adjuvant chemotherapy with CHOP as first line. One patient progressed on CHOP but achieved pathological complete response (pCR) with Brentuximab Vedotin. After a mean follow-up of 23 months (range: 1–56) all patients reported here remain disease-free. Discussion: BIA-ALCL is a rare neoplasm with a good prognosis. Our data support the recommendation that stage I disease be managed with surgery alone. Adjuvant chemotherapy may be required for more invasive disease and our experience has shown the efficacy of Brentuximab as a second line treatment.